Knowledge domain and emerging trends in post-stroke cognitive impairment: a bibliometric analysis - Heyu Zhang; Yanwei Li; Luqian Zhan; Jingfang Long; Jianing Shen; Jiahui Chen; Jiajing Qian; Zhiming Pan; Xue Wu; Zhen Wang; Zhen Wang; Wenjun Wu; et al. (Frontiers in Aging Neuroscience)
BackgroundCognitive impairment is an important cause of disability and death among the elderly. One of the most important risk factors is stroke. Post-stroke cognitive impairment (PSCI) not only diminishes the quality of life for patients but also increases the burden on families and society. But PSCI can be mitigated through early intervention. Cerebral small vessel disease (CSVD) is one of the significant causes of stroke and has garnered considerable attention in PSCI. Therefore, this study aims to identify research priorities and trends in PSCI through bibliometric analysis, and further explore the role played by CSVD in PSCI.MethodsIn this study, we performed a systematic search in the Science Citation Index Expanded (SCI-E) of the Web of Science Core Collection (WoSCC). VOSviewer, CiteSpace and Origin were mainly used to visualize the research focus and trend in PSCI. In addition, we screened the retrieved literature again, and performed keyword analysis on the studies related to CSVD.ResultsA total of 1,943 publications were retrieved in the field of PSCI in this study, with consistent upward trend in annual publications in recent years. Pendlebury was an important leader in PSCI research. Capital Medical University was in the leading position judging from the number of publications. China had the highest number of publications in this field. The journal Stroke had the strongest international influence in this field. Keywords such as “functional connectivity,” “tool,” “systematic review,” and “meta-analysis” have been revealed to have momentous impact on PSCI in recent years. In the further analysis of PSCI and CSVD, “hypertension,” “white matter hyperintensities (WMH),” “cerebral microbleeds (CMBs),” and “cerebral amyloid angiopathy (CAA)” received extensive attention.ConclusionThe study of PSCI is still in the development stage. This study systematically summarizes the progress and development trend in the field of PSCI, and further explores the relationship between CSVD and PSCI through hypertension and magnetic resonance imaging markers. This study is of great significance for researchers to quickly understand the development of PSCI, but also helps them understand future directions, and provides important insights for the prevention and treatment of PSCI.